Inclusive Education as a Condition for Innovative Activities at Higher Education Institutions - Bahno, Yuliia M.; Serhiichuk, Olena M.; Tanana, Svitlana M.; Tkachenko, Larysa V.; Khmelnytska, Olena S. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
This study discusses the activities of higher education institutions in the context of inclusive education as an innovative approach. The introduction of inclusive education in the modern higher education system is highly important. The existing specialised education system is undergoing changes resulting in new requirements for work with people with special educational needs in various areas. The purpose of this study is to consider the mechanism of implementation of inclusive education in the activities of higher education institutions, which ensures accessibility and requires high-quality education, in particular, taking into account the educational needs of every individual. The problems of the educational process faced by the students are analysed in detail. This study justifies the necessity of introducing inclusive education in modern educational systems, describes positive experiences of some higher education establishments, provides a step-by-step analysis of the introduction of inclusive education in higher education institutions in Ukraine and defines promising areas for its implementation. This study’s theoretical and methodological basis included the works of the world’s leading scientists and a regulatory framework for inclusive education. The article presents students’ attitudes to the implementation of inclusive education. To achieve these objectives, the analysis of the latest research on the implementation of the right to education of persons with special educational needs was carried out. The study results showed a positive attitude towards inclusive education and joint education of people with special educational needs. The study found that inclusive education requires more time and effort to organise the educational process. The introduction of inclusive education elements can increase the efficiency of this process. The effective use of the methods to implement inclusive education in higher education institutions contributes to achieving its goals and results. The introduction of inclusive education provides an effective operational analysis of training quality for students with special educational needs and educational process adjustments, which ultimately creates a management system.